Employees' behaviour on smoke-free policy - Abdul Manan, Kamaruzzaman; Ahmad, Che Mahzan (IIUM Press, International Islamic University Malaysia, 2017)
This book contributes towards the body of knowledge in addressing smoking as one of the problems of the employees. This idea corresponds with the suggestions that are mentioned by Antero, Maritta, Erkki and Kari (2001) whereby in order to go forward in achieving the smoke-free workplace objectives, more research should be conducted to understand the actual conditions of employee’s problems, attitudes and life patterns. Smoking is one of the avoidable problems faced by Malaysian societies (Lee & Tam, 2014). However, there is still scarcity of studies from the Malaysian tobacco consumption perspectives. This book measures the extent of employees’ knowledge, attitude and behaviour of the smoke-free policy and will enhance the understanding of tobacco cessation issues from the employee’s perspective. Employees are assets that allow the organisation’s operations to run smoothly. In order for the policy to be internalised by its community, the public university has to ensure that employees are able to understand, support and behave accordingly with the policy objectives. Suffice to say, the behaviour on the existing policy is necessary for future policy improvement. Even though the public university has been conducting smoking behaviour research at the national level, it has never conducted a research on smoking behaviour of its own employees. This study will help the public university to examine the employee behaviour that are important in helping the public university to plan and improve the existing campaign in order to free the campus from tobacco. As for the theoretical contributions, this book incorporates the Theory of Planned Behaviour (TPB) variables with the three background factors of workplace health knowledge that include comprehensive smoke-free workplace, strategic health communication and tobacco hazard with the aim to provide a better understanding of the reality in behavioural phenomena, in particular employees’ behaviour on the public university smokefree policy.